(untitled) (Revista da Faculdade de Odontologia - UPF, 2018)
Objective: to verify the accuracy of cone beam computedtomography (CBCT) for measuring dentin thicknessin the danger zone of mandibular molars in order to validatethis method to be used as a clinical auxiliary. Materialsand method: dentin thickness of the distal wall ofmesial canals was measured at 2 mm of furcation areain ten mandibular molars before and after preparation ofcervical and middle thirds. CBCT (0.25 mm voxel size)and stereomicroscopy images were acquired twice foreach sample. CBCT axial images and stereomicroscopeimages were evaluated by a calibrated examiner. Statisticalanalysis was performed using Mann-Whitney testin order to investigate whether CBCT images providedtrusted values. Results: mean values of initial (1.23 versus1.24 mm) and final measurements (0.88 versus 0.87mm) obtained with, respectively, CBCT and stereomicroscopemethods did not show statistical differences(P > 0.5). Conclusion: CBCT images provide high accuracyfor measuring dentin thickness in the danger zoneof mandibular molars.Keywords: Cone beam computed tomography. Endodontics.Root canal preparation.